The potency of Sentinel-2 satellite for monitoring during and after coral bleaching events of 2016 in the some islands of Marine Recreation Park (TWP) of Pieh, West Sumatra. (May 2019) - Wouthuyzen, Sam; Abrar, M; Corvianawatie, C; Salatalohi, A; Kusumo, S; Yanuar, Y; Darmawan,; Samsuardi,; Yennafri,; Arrafat, M Y
Abstract: The coral bleaching event (CBE) which trigerred by increase in sea temperatures of 1-2˚C during El-Nino can make corals stressful or potentially dead. Many CBE research are conducted using sea temperature data measured through infrared thermal (TIR) satellite sensor. However, very few study use optical remote sensing data. This study aim to analyze the potential of optical Sentinel-2 (S-2) satellite data for monitoring during (Jun. 2016) and after (Jun. 2018) CBE in small islands of marine protected areas (TWP) of Pieh. A series image analysis procedure was conducted, i.e. simple DOS atmospheric correction; normalizating digital numbers (DN) of Blue, Green and Red bands of subject images during and after CBE to the reference image (before CBE. Dec. 2015) using "pseudo invariant feature (PIF)" approach; subtracting the DN of each bands of images during and after CBE to the reference image, and generating color composite of natural color with a contrast stretch. Result showed that this procedure can detected clearly the CBE. There was an average decreasing bleaching trend of 1.63 ha (15.8%), which indicated that some corals have recovered from thermal stress inside the TWP of Pieh. However, islands outside the TWP of Pieh, showed an increasing trend by an average of 0.50 ha (21.2%). The predation corals by the crown of thorn seastar, Acanthaster planci, whose population exploded after CBE was the main reason why CBE still detected both inside and outside the TWP of Pieh. This study shows the ability and potency of optical remote sensing data of S-2 satellite to monitor CBE, but need a lot of validation from many other sites. This result is very useful for supporting project such as COREMAP CTI.